Probiotic utilization enhances vannamei (Litopenaeus vannamei) growth and survival ratio during dry and rainy season - Budiman Budiman; Fadly Irmawan; Lukas Wibowo Sasongko; Frangky Fransiskus Tumion (Depik, 2025)
The study was conducted at the Vannamei Shrimp Pond Unit of the Pontianak State Polytechnic Technology Excellence Center, Mempawah Regency, and the Vannamei Shrimp Enlargement Unit of the Vocational and Nautikan High School, Sambas Regency. The study aims to determine the growth performance and survival of vannamei shrimp feed conversion intensively raised using probiotics in the dry season (March-August) and the rainy season (September-February) in 2022-2023. PL-15 vannamei shrimp fry were stocked at a density of 120/m2 in 2 pond plots with an area of 2,500 m2 and 2 pond plots of 3000 m2. The data collection method used observation and participation in the cultivation process, starting from land preparation, feed management, and water quality to harvest. The data were analysed descriptively, and a literature review was conducted to compare the technical activities applied in the field with the supporting theoretical basis. From the 120-day maintenance activity in the dry season, the average value of SR was 98.27%, biomass 26,749.7 kg, ABW 41.58 gr/pcs, ADG 0.27 gr/pcs, this shows relatively better results when compared to the rainy season maintenance period with an average value of SR 85.73, Biomass 20,794.6 kg, ABW 35.11 gr/pcs, ADG 0.21gr/pcs.Keywords:ProbioticsVannamei ShrimpIntensiveDry SeasonRainy Season